Mycorrhizal inoculation affects the phytochemical content in strawberry fruits - Ana Paula Cecatto; Fátima Martínez Ruiz; Eunice Oliveira Calvete; Jesús Martínez; Pedro Palencia (Acta Scientiarum. Agronomy, 2016)
The aim of this research was to evaluate the effect of the inoculation date of arbuscular mycorrhizal fungi on the fruit quality and the content of phytochemicals in a strawberry soilless growing system. The experiment was performed in Huelva (Spain) and was conducted in a greenhouse on the La Rábida Campus of Huelva University under natural light and temperature from October 2013 to June 2014. Three short-day strawberry cultivars (‘Splendor’, ‘Sabrina’ and ‘Fortuna’) were grown in polyethylene bags filled with coconut fibres. Randomized block design, with 3 repetitions and factorial arrangement (3 cultivars x 3 treatments), was established. Each replicate consisted of one bag with 12 plants supporting structures at 40 cm height. The treatments were: T1 = mycorrhizal inoculation in the transplantation; T2 = mycorrhizal inoculation 30 days after transplantation (DAT); and T0 = control treatment, without inoculation. Arbuscular mycorrhizal fungi inoculation significantly affected the contents of anthocyanin and phenolics. When the inoculation is performed in the transplantation, the fruits showed a high content of anthocyanin and total phenolics. The mycorrhizal inoculation influences decreasing the acidity in fruit throughout the growing season and increase firmness only during the early stage of production.